A door sub-system sled test methodology for simulation of occupant responses in FMVSS 214 side impact oblique pole test. (9th November 2009) - Aekbote, K.; Zhao, L.; Maltarich, M.; Cheng, J.; Chou, C.C.; Yang, K.H.
This paper describes the development of a new door subsystem sled test methodology to simulate the occupant responses in NHTSA's 75° oblique pole side impact test mode using SID-IIs and ES-2re dummies. This sled subsystem test methodology consists of a door sled oriented at 75°, with the dummy on a seat located at the same distance from the door as in full-vehicle test, to simulate gap closure for evaluating side airbags. The door sled is accelerated to an initial velocity of 20 mph and then impacts the stationary pole. From the onset of door contact with the pole, the velocity of door sled is decelerated following the non-struck side velocity of the vehicle by means of VIA decelerator. The validation of the test methodology with both SID-IIs and ES-2re dummies is presented by comparing their respective responses between the sled subsystem and full-vehicle tests.